2013
DOI: 10.1111/flan.12023
|View full text |Cite
|
Sign up to set email alerts
|

Does Beginning Foreign Language in Kindergarten Make a Difference? Results of One District's Study

Abstract: Educators have generally believed that foreign language instruction should begin in kindergarten or earlier to promote optimum oral language development (e.g., Abbott, ; Curtain & Dahlberg, 2010; Rhodes & Pufahl, ; Rosenbusch, ; Swender & Duncan, ). This article describes two Spanish programs in the Westport (Connecticut) Public Schools district: their new, long‐sequence K–8 program and the short‐sequence Grade 5–8 program it replaced. A five‐year study examined students' oral and listening comprehension profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 11 publications
5
24
0
Order By: Relevance
“…They found that more than 75% of eighth graders who participated in the K-8 cohort were able to speak Spanish at the sentence level, while less than half of the eighth graders (45.5%) from the grades 5-8 cohort were able to speak in sentences. This study provided empirical data to support the claim that younger students can attain higher proficiency levels than those who begin WL study later (Boyson et al, 2013). Muñoz (2011) found conflicting evidence to Boyson et al (2013), which was more aligned with Kuhl's (2011) neuroscience research, when she studied the effects of language input and starting age with 162 undergraduate English majors who were 30 years old or younger and had studied English for 10 or more years.…”
Section: The Starting Age Controversy In Language Learningmentioning
confidence: 63%
See 3 more Smart Citations
“…They found that more than 75% of eighth graders who participated in the K-8 cohort were able to speak Spanish at the sentence level, while less than half of the eighth graders (45.5%) from the grades 5-8 cohort were able to speak in sentences. This study provided empirical data to support the claim that younger students can attain higher proficiency levels than those who begin WL study later (Boyson et al, 2013). Muñoz (2011) found conflicting evidence to Boyson et al (2013), which was more aligned with Kuhl's (2011) neuroscience research, when she studied the effects of language input and starting age with 162 undergraduate English majors who were 30 years old or younger and had studied English for 10 or more years.…”
Section: The Starting Age Controversy In Language Learningmentioning
confidence: 63%
“…In a five-year longitudinal study, Boyson et al (2013) examined elementary students' oral and listening proficiency levels from two Spanish programs in an affluent public school district in Westport, Connecticut at the end of fifth and eighth grade. Boyson et al (2013) claimed that teachers employed communicative methods, such as using the target language 95 to 100% of the time, making content comprehensible through gestures and visual aids, and teaching students strategies to use for communicating in the target language.…”
Section: The Starting Age Controversy In Language Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers agree that early childhood is a critical period for language learning and development (e.g., Andersson, 1974;Nikolov, 2009), not only in L1 but also in L2 (Boyson, Semmer, Thompson, & Rosenbusch, 2013), even in a situation of minimal exposure to L2 (Larson-Hall, 2008) since the basic process of language acquisition such as first words or first use of grammar (Bialystok, Craik, Green, & Gollan, 2009) does not differ whether one or two languages are being acquired (Werker, 2012). It has been suggested that L2 education begin early in life since young children find it easier to pick up a new language (Nikolov 2009) than do adults.…”
Section: Literature Reviewmentioning
confidence: 99%